The Relevance of Islamic Education Concept Abdul Karim Amrullah's Perspective in the Contemporary Era - Wahyudi, Sahidin; Fatoni, Ahmad (CV. Tripe Konsultan, 2024)
The purpose of this study is to investigate the applicability of Abdul Karim Amrullah's conception of Islamic education in the modern day. Using a descriptive-qualitative methodology, this study examines a number of works that address the applicability of the idea of Islamic education from the viewpoint of Abdul Karim Amrullah in the modern period. The study's findings demonstrate that the curriculum or educational system put in place by Haji Rasul is still regarded as